Dislocated interests and climate change. (31st May 2016) - Davis, Steven J; Diffenbaugh, Noah
Abstract: The predicted effects of climate change on surface temperatures are now emergent and quantifiable. The recent letter by Hansen and Sato (2016 Environ. Res. Lett. 11 034009 ) adds to a growing number of studies showing that warming over the past four decades has shifted the distribution of temperatures higher almost everywhere, with the largest relative effects on summer temperatures in developing regions such as Africa, South America, southeast Asia, and the Middle East (e.g., Diffenbaugh and Scherer 2011 Clim. Change 107 615–24 ; Anderson 2011 Clim. Change 108 581 ; Mahlstein et al 2012 Geophys. Res. Lett. 39 L21711 ). Hansen and Sato emphasize that although these regions are warming disproportionately, their role in causing climate change—measured by cumulative historical CO2 emissions produced—is small compared to the US and Europe, where the relative change in temperatures has been less. This spatial and temporal mismatch of climate change impacts and the burning of fossil fuels is a critical dislocation of interests that, as the authors note, has 'substantial implications for global energy and climate policies.' Here, we place Hansen and Sato's 'national responsibilities' into a broader conceptual framework of problematically dislocated interests, and briefly discuss the related challenges for global climate mitigation efforts.